Спікання при високому тиску порошків тугоплавких сполук титану і цирконію - Коновал, С.М.; Гарбуз, Т.О.; Кріштова, О.В.; Беженар, М.П.; Божко, С.А.; Білявина, Н.М. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
The phase composition, real crystalline structure and properties of the polycrystals sintered in HPA under temperatures 1300–2300 K and pressures 2,5–7,7 ГПа of powders of refractory compounds TiB2, TiC, TiN, ZrN are explored. Formation on the basis of their crystalline lattices of solid solutions of oxygen is indicate. The factors influencing hardness of polycrystals are analyzed.